EKSPOR KARBON DARI SERASAH DAUN MANGROVE DI TAMAN NASIONAL RAWA AOPA WATUMOHAI - Analuddin Analuddin; Jamili Jamili; Dafid Pratama (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2016)
ABSTRACTMangrove ecosystems are highly productive and contribute as sources organic carbon and nutrients. The present study was aimed to determine export of of carbon from R. mucronata and C. tagal mangrove leaf litter at Rawa Aopa Watumohai National (RAWN) Park. Litterfall sampling of mangrove at RAWN Park was done by purposive sampling method. Carbon content was analyzed using ash method. The export value of carbon and nitrogen was estimated. The results showed that monthly export of organic carbon by mangrove C. tagal (14,36 g C/ m2/month) was higher than R. mucronata (12,02 g C/m2/month. Therefore, R. mucronata and C.tagal play important role as source of carbon and support the coastal ecosystem productivity.Keywords : Mangrove Forest, Leaf Litter, Carbon Export, RAWN Park.